Clinical Features and Outcome of Mucormycosis - Camara-Lemarroy, Carlos Rodrigo; González-Moreno, Emmanuel Irineo; Rodríguez-Gutiérrez, René; Rendón-Ramírez, Erick Joel; Ayala-Cortés, Ana Sofía; Fraga-Hernández, Martha Lizeth; García-Labastida, Laura; Galarza-Delgado, Dionicio Ángel (Interdisciplinary Perspectives on Infectious Diseases, 2014)
Mucormycosis (MCM) is a life-threatening infection that carries high mortality rates despite recent advances in its diagnosis and treatment. The objective was to report 14 cases of mucormycosis infection and review the relevant literature. We retrospectively analyzed the demographic and clinical data of 14 consecutive patients that presented with MCM in a tertiary-care teaching hospital in northern Mexico. The mean age of the patients was 39.9 (range 5–65). Nine of the patients were male. Ten patients had diabetes mellitus as the underlying disease, and 6 patients had a hematological malignancy (acute leukemia). Of the diabetic patients, 3 had chronic renal failure and 4 presented with diabetic ketoacidosis. All patients had rhinocerebral involvement. In-hospital mortality was 50%. All patients received medical therapy with polyene antifungals and 11 patients underwent surgical therapy. Survivors were significantly younger and less likely to have diabetes than nonsurvivors, and had higher levels of serum albumin on admission. The clinical outcome of patients with MCM is poor. Uncontrolled diabetes and age are negative prognostic factors.